Research with yam bean (Pachyrhizus erosus) and its potential for the agricultural growth of the agricultural growth of the region. - Mora, Antonio; Morera, Jorge (Agronomía Mesoamericana, 2016)
The yam bean (Pachyrhizus erosus) is an excellent alternative crop for the agricultural diversification in the American tropics, because the tuberous roots can be used as food and natural insecticides are produced with the rotenone extracted from the seeds. The main object of this trial was to submit the latest research findings obtained from the testing of new yam bean genotypes, under different environments in Costa Rica. Three experiments were established during April and July of 1993: 10 genotypes were evaluated at two localities, Alajuela and Turrialba, in the first two trials. The third trial conducted in Turrialba consisted of planting distances (0.10,0.15 and 0.20 m between plants. As a whole, there is a marked tendency with respect to the locality, as it was proven in consecutive trials that Alajuela is the most appropiated zone for growing yam bean. With reference to planting distances, the preliminary results suggest that at shorter distances, the larger the root production and the lower their weight. The yam bean offers an alternative to be considered for the agricultural development of the region because of itsadaptation within the farmers’, systems, improving the food sustainability.